Thermal performance of a solar-aided latent heat store used for space heating by heat pump - Esen, M (Pergamon-Elsevier Science Ltd, 2000)
In this study, the cylindrical phase change storage tank linked to a solar powered heat pump system is investigated experimentally and theoretically. A simulation model defining the transient behaviour of the phase change unit was used. In the rank, the phase change material (PCM) is inside cylindrical tubes and the hear transfer fluid (HTF) flows parallel to it. The heat transfer problem of the model (treated as two-dimensional) was solved numerically by an enthalpy-based finite differences method and validated against experimental data. The experiments were performed from November to May in the heating seasons of 1992-1993 and 1993-1994 to measure both the mean temperature of water within the tank and the inlet and outlet water temperature of the rank. The experimentally obtained inlet water temperatures are also taken as inlet water temperature of the simulated model. Thus, theoretical temperature and stored heat energy distribution within the tank have been determined. Solar radiation and space heating loads for the heating seasons mentioned above are also presented. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: Phase-Change Materials; Energy-Storage; Systems